THE EFFECT OF PLYOMETRICS TRAINING ON LEG MUSCLE STRENGTH OF MEDICAL STUDENTS IN DIPONEGORO UNIVERSITY - Nur Azzahra Permata Putri Ismail; Edwin Basyar; Darmawati Ayu Indraswari; Marijo Marijo (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2019)
Introduction : Strength is the ability to excert force, which can resist external resistance and its purpose as a basis for human movements. Strength also can be a standard for measuring someone’s performance. Plyometrics training known as an exercise that can increased muscle strength. Great muscle strength can lead to great muscle endurance so that the person will become healthier and will not get tired easily. However, there’s still no further study that measured leg muscle strenght on medical students after given plyometrics training treatment. Methods : Intervention of the study was plyometrics training for 6 weeks. This study was a quasi-experimental with pre-test (before training), middle-test (after four weeks training), and post-test (after six weeks training). The subjects were 28 (15 to 25-year old) male medical students of Diponegoro University divided into 2 groups with 14 samples for each group: control group and treatment group. Muscle strength were measured by leg dynamometer. The results were analyzed using SPSS. Results : The muscle strength which measured by leg dynamometer improved among subjects who did plyometrics training. The significant results (P = <0,05) found on middle-test and post-test proved that plyometrics training affects the enhancement of leg muscle strength. Conclusions : Plyometrics training for 6 weeks proved to increase leg muscle strength of medical students in Diponegoro University.Keywords: Plyometrics Training, Strength, Leg Dynamometer